Evaluation of the Impact of the Public-Private Partnership Program in Economic Infrastructure Development - Amir, Khaeriah (Professorline, 2025)
This study examines the impact of Public-Private Partnership (PPP) programs on economic infrastructure development in Indonesia using a mixed methodological approach and a multi-dimensional evaluation framework. Based on an analysis of 30 PPP projects implemented during the period 2010-2023, the study finds that the PPP model produces an average cost efficiency of 17.3% higher and project completion is 22% faster than conventional procurement. Econometric analysis confirms a significant positive correlation between PPP investment and regional economic growth with an elasticity coefficient of 0.28 ( p<0.01). However, the geographical distribution of PPP projects is still concentrated in Java Island (62%), indicating inequality in program implementation. Multi-criteria evaluation using the Composite Performance Index (CCI) shows performance variations across sectors with telecommunications scoring the highest (74.2 ) , followed by energy (71.8), transportation (65.3), and water (58.2). Factor analysis identifies the governance dimension as the largest contributor to PPP success (38% of the variance), while the environmental dimension consistently scores the lowest. Eight critical factors for the success of PPP implementation were identified, including the quality of project preparation, proportional risk allocation, and long-term political commitment. Key challenges in PPP implementation include suboptimal inter-agency coordination, limited government technical capacity, and a regulatory framework that needs to be improved. The study concludes that the PPP model has significant potential to accelerate infrastructure development, but requires comprehensive policy reforms in institutional, regulatory, and capacity-building aspects to optimize its benefits for inclusive and sustainable economic development.